The Challenge of ESL Writing: Understanding Learners’ Anxiety in Writing Classrooms - Ubaid Ullah Ubaid,; Sayyed Rashid Ali Shah,; Irfan Bashir,; Khalid, (Al-Qanṭara, 2023)
English language writing proficiency is essential for learners’ personal, professional, and academic growth. Notably, in a country like Pakistan, English is used and taught as an official and second language from grade one. However, after learning English for more than 10 years, Pakistani undergraduates still lack appropriate writing skills which ultimately leads to their feeling of uneasiness and anxiety in classroom. Thus, the aim of this study is two-fold: First, to investigate the levels of writing anxiety of Pakistani English as a second language (ESL) undergraduates; Second, to discover the factors that may contribute to the writing anxiety of Pakistani ESL undergraduates. A mixed-methods approach was utilised. The quantitative data was collected from 250 participants through a purposive sampling method using Second Language Writing Anxiety Inventory (SLWAI) and five participants were recruited for the semi-structured interviews. The results obtained from the questionnaire revealed that Pakistani undergraduates experienced a high level of somatic and cognitive anxieties in ESL writing. However, the level of their avoidance behaviour was moderate. The semi-structured interviews revealed various administrative, academic and pedagogical factors that contributed to the undergraduates’ writing anxiety. These factors included lack of self-confidence, time constraints, weak language skills, frequent assignments, teachers’ feedback, fear of assessment, lack of writing practice, pressure to be perfect, topic familiarity, inadequate writing techniques, and classroom environment. Based on the findings, this study provides pedagogical implications for ESL teachers. Keywords: Anxiety, ESL learners, mixed-methods, productive skills, writing